Palliative and End-of-Life Interventions for People Experiencing Homelessness: A Mixed-Methods Systematic Review - Ingle, M. Pilar; Traver, Anthony; Calhoun, Katie Hoops; Cutforth, Asia; Johnson, Ian M. (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Despite the benefits of palliative and end-of-life (PEOL) care for individuals with serious and terminal illness, barriers to accessing this form of care persist among adults experiencing homelessness. Seriously ill unhoused individuals die at younger ages than stably housed individuals, are less likely to be receiving comprehensive care, and are more likely to die in unsupportive settings. Strengthening the evidence base for PEOL interventions for adults experiencing homelessness may help inform the development and implementation of future programs, ultimately improving this population’s access to PEOL care. The objective of this mixed-methods systematic review is to summarize the literature of PEOL interventions and programs for unhoused adults and identify barriers and facilitators for developing, implementing, and maintaining these interventions. Six databases and gray literature were searched to identify programs between December 2023 and February 2025. The search produced 407 articles; 30 met inclusion criteria and were assessed and synthesized using a convergent integrated approach. A total of 21 unique programs were described across the articles, including interventions focused on advanced care planning, service provider support, mobile palliative care, fixed-site services, and systemic strategies. Common barriers for program success included lack of funding or staff support, lack of buy-in from participating providers, an overall lack of resources available for unhoused individuals, and insufficient engagement with unhoused communities. Conversely, multi-agency and cross-disciplinary collaboration, community support, workforce training and support, and financial or organizational support were commonly identified as facilitators for program success. More financial and organization support are needed for the successful development and long-term success of PEOL programs for people experiencing homelessness. Future research should use implementation science to identify best practices for the development, implementation, and maintenance of evidence-based PEOL programs.